Transbronchial catheter aspiration compared to forceps biopsy in the diagnosis of peripheral lung cancer - Franke K-J; Nilius G; Ruhle K-H (European Journal of Medical Research, 2009)
Abstract Objective The usual procedure for obtaining material for histological analysis for the diagnosis of peripheral carcinoma of the lung is transbronchial forceps biopsy (TBB). Not widely spread is acquiring samples for cytological examination by transbronchial catheter aspiration (TBCA). Data were retrospectively collected to determine the diagnostic sensitivity of TBCA in comparison with TBB concerning malignancy. Methods We analysed the results of 51 consecutively examined patients (age 68.7 ± 8.8 yrs.) applying both methods. 48 of 51 peripheral lesions proved to be malignant, 34 of which measured > 3 cm in diameter and 14 ≤ 3 cm. Fluoroscopy provided guidance in biopsies for both techniques. Results The mean diameter of the lesion was 3.7 ± 1.5 cm. We were able to establish a correct diagnosis by TBCA in 36 of 48 patients with lung cancer, and in 21 of 48 patients by TBB (75% vs. 44%, p < 0.01, chi-square-test). By combination of both methods 39 of 48 patients were correctly diagnosed. For carcinoma > 3 cm the success rate for TBCA was 76% (26/34) and for TBB 56% (19/34). For carcinoma ≤ 3 cm the success rate for TBCA was 71% (10/14) and for TBB 14% (2/14). Conclusions Even in lesions ≤ 3 cm application of TBCA results in an only marginally lower success rate compared to lesions > 3 cm. Due to the overall high success rate we suggest to apply the easy-to-handle and inexpensive method of TBCA in diagnostic procedure of peripheral lung carcinoma.